Longitudinal structural changes in the optic nerve in ischemic optic neuropathy: a case report - N.M. Moyseyenko (Journal of Ophthalmology, 2025)
Purpose: To describe the case of longitudinal structural changes in the optic disc in ischemic optic neuropathy.